T-cell and antibody responses to first BNT162b2 vaccine dose in previously infected and SARS-CoV-2-naive UK health-care workers: a multicentre prospective cohort study - Angyal, A; Longet, S; Moore, SC; Payne, RP; Harding, A; Tipton, T; Rongkard, P; Ali, M; Hering, LM; Meardon, N; Austin, J; Brown, R; et al. (Elsevier, 2021)
Background Previous infection with SARS-CoV-2 affects the immune response to the first dose of the SARS-CoV-2 vaccine. We aimed to compare SARS-CoV-2-specific T-cell and antibody responses in health-care workers with and without previous SARS-CoV-2 infection following a single dose of the BNT162b2 (tozinameran; Pfizer–BioNTech) mRNA vaccine.